Report of the CTA/CRFM Training of Trainers Workshop for Fisheries Extension Officers to Enhance Their Skills to provide better Information, Advisory and Training Services to Primary and National Fisherfolk Organizations - Caribbean Regional Fisheries Mechanism (CRFM, 2007)
This training is is aimed at enhancing the capacities of twenty-four fisheries extension officers in twelve ACP/CRFM Member States (Groups 1 and 2) to provide better information, advisory and training services to primary fisherfolk and national fisherfolk